Controlled synthesis and properties of layered double hydroxides - Wang, C; Chengle Wang (2012)
The aims of this thesis are concerned with the synthesis of layered double hydroxide nanoparticles with controlled morphology and particle size distribution and an investigation of their physical properties. An introduction of layer double hydroxide chemistry, especially existing synthetic approaches, is reviewed in Chapter 1. Structural investigations, characterisation techniques, the properties and the applications of LDHs are discussed consecutively. The first successful synthesis of lithium aluminium nanorods using the hydrothermal treatment of a gibbsite precursor with a rod-like morphology is described in Chapter 2. The rod morphology is depicted using electron microscopy and confirmed by comparing refined X-ray diffraction patterns to a standard sample. Chapter 3 describes the application of reverse microemulsion method to prepare Co-Al and Ni-Al LDH nanoplatelets. The LDH particle sizes can be effectively controlled, and the structures of the nanoplatelets are investigated. The magnetic properties of the LDH nanoplatelets are dependent on the size of the nanoplatelets. A novel single component microemulsion system for the synthesis of LDHs is developed in Chapter 4. Mg-Al LDH nanoplatelets were successfully synthesised with precise particle size control. The factors affecting the formation of the microemulsions and the mechanism of the synthesis are discussed. Chapter 5 focuses on the applications of the novel single component microemulsion methods to prepare a range of LDHs with different metal combinations including Co-Al, Ni-Al, Zn-Al, Li-Al, Ca-Al, and Ni-Fe. This method proves very effective at controlling the particle sizes. The magnetic properties of the LDHs containing paramagnetic transition metal centres have been studied in detail. In Chapter 6, the DIFFaX program has been used to simulate the XRD patterns of layered structures. The factors influencing the XRD patterns in these materials have been systematically investigated including the effects of particle size, stacking faults, and disorder. The XRD patterns of materials described in previous chapters are simulated using the latest DIFFaX+ code in order to estimate the particle sizes and stacking sequences. The characterising techniques and the experimental details are listed in Chapter 7.